Corporate social responsibility: model in Germany - Nosova, O. V.; Nosova, T. Y. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article focuses on the concept of corporate social responsibility research in Germany. In the world practice the concept of corporate social responsibility of business has become synonymous to the concept of an effective and transparent business with sustainability effects. Corporate social responsibility is considered as the ability of an organization or an enterprise to evaluate the consequences of their actions for sustainable social development. German multinationals have more positive public image, enhance a modal of profitability, and show the benefits of corporate investments in society.Presenting the challenges and perspectives of corporate social responsibility the authors examine the current state and future directions of the development of German multinationals. The aim of the article is to define the typical features of the model of corporate social responsibility in Germany and proposes its application for Ukrainian companies. The theoretical section includes economic analysis of the methods and tools of German multinationals. The authors prove that the analysis of the basic features of German corporate social responsibility model can be applied for emerging economies in order to ensure competitiveness, high level of productivity and profitability. The institutions of corporate social responsibility  can be used to address critical economic, social and environmental issues, and to act in favor of the development of the national economy. The authors emphasize the necessity of qualitative changes in the institutional environment that will promote entrepreneurial activities and economic growth.